An Annotated Checklist of Vascular Plants of Gulmarg Wildlife Sanctuary, Kashmir Himalaya - Wani, Zishan Ahmad; Kumar, Shailesh; Islam, Tajamul; Pant, Shreekar (Phytotaxa, 2026)
The present study aimed to document the vascular plant diversity of Gulmarg Wildlife Sanctuary (GWLS), and provide detailed information on each species, including correct nomenclature, family, growth form, Raunkiaer life form, elevational range, nativity and endemism, as well as IUCN status. A total of 344 vascular plant species, representing 226 genera and 104 families, were recorded, indication a high level of floristic richness in the study area. Asteraceae was found to be the dominant family, and the vegetation composition was primarily herbaceous. Out of the total plant species recorded, 159 were native to the Himalayan region, including 79 endemics, highlighting the strong biogeographical uniqueness of the flora. The hemicryptophytes were the most abundant life form, followed by phanerophytes, reflecting the strong ecological adaptation of the local flora to cold and seasonally harsh climatic conditions. Both native and non-native species showed a negative relationship with elevation, indicating elevational constraints on their distribution. However, the decrease in richness of non-native species was more pronounced and statistically significant (R2 = 0.83, p < 0.001). The distribution of Levins’ niche breadth (B) further revealed differences between native and non-native plant species along the elevational gradient. Of the 344 plant species recorded, only 46 have been assessed for the IUCN Red List, among which 8 species are categorized as threatened. Nearly 86% of the recorded flora remains unassessed highlights a significant information gap in regional conservation planning. These findings underscore the urgent need for region-specific conservation strategies to safeguard the Himalayan plant diversity and maintain the ecological stability of this globally significant mountain ecosystem.